Synthesis and in vitro evaluation of spirobenzovesamicols as potential 11C-PET tracer alternatives to [18F]FEOBV for vesicular acetylcholine transporter (VAChT) imaging - Hugo Helbert; Winnie Deuther-Conrad; Michel de Haan; Barbara Wenzel; Gert Luurtsema; Wiktor Szymanski; Peter Brust; Rudi A. J. O. Dierckx; Ben L. Feringa; Philip H. Elsinga (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Through its central role in neurotransmission, the vesicular acetylcholine transporter (VAChT) is an increasingly valuable target for positron emission tomography (PET). VAChT ligands have been mostly derived from the vesamicol structure, but with limitations in available labelling methods and selectivity for VAChT against σ receptors being a common pitfall of such compounds, the development of selective VAChT tracers remains a challenge. Modern labelling techniques, in this case the [11C]MeLi cross-coupling methodology, expands labelling opportunities, allowing to explore novel vesamicol-based structures as potential PET-tracers. Results A series of vesamicol derivatives was synthesized and their binding towards VAChT, σ1 and σ2 receptors assessed. Of all compound tested, (-)-2-methylspirobenzovesamicol ((-)-4) was the most promising with a 16 ± 4 nM affinity towards VAChT, a 29-fold weaker affinity for σ1 receptors and negligible binding (> 1 μM) towards σ2 receptors. The radiolabelling was performed from the corresponding bromide using a [11C]MeLi cross-coupling protocol, yielding 2-[11C]methylspirobenzovesamicol in 32–37% RCY. New in vitro binding data is also made available for (-)-FEOBV with human-sourced σ1 receptors, revealing a 300-fold stronger affinity for VAChT compared to σ receptors. Conclusion (-)-2-methylspirobenzovesamicol was identified as a potent and selective VAChT ligand, with moderate to low affinity for σ receptors, and its racemate was radiolabeled in good radiochemical yields with Carbon-11. At this stage, [11C]-methyl-2-methylspirobenzovesamicol appears a promising 11C-PET tracer for VAChT imaging.